Internalization of Religious Values in Storytelling Tradition at BA 'Aisyiyah Bajong - Khasiroh, Siti (International Proceedings of Nusantara Raya, 2022)
Advances in technology, the influence of the screen era, globalization and the Covid-19 pandemic have had a very extraordinary impact, one of which can be felt in the world of Early Childhood Education. Many children experienced a decline, in terms of learning motivation, habits, attitudes and morals of children which resulted in low religious values ​​children. The tradition of storytelling at BA 'Aisyiyah Bajong is one of the programs integrated into the literacy-based learning model. This program seeks to instil and develop religious values ​​for early childhood. This writing aims to explain the implementation of the storytelling tradition and its benefits in developing religious values ​​for early childhood. This writing uses a qualitative approach with a descriptive method. Data were collected through observations of program implementation and interviews with educators, children and parents. Data analysis used descriptive analysis. The results of the writing found that the tradition of storytelling was carried out in a planned and programmed manner by integrating it into a literacy-based learning model. This program is implemented in institutions by educators and at home with parental involvement. Storytelling activities are carried out through various techniques according to early childhood development which is presented in an interesting and fun way. The implementation of the storytelling tradition is supported by the facilitation of literacy corner facilities in schools and storytelling areas at home. This program involves parents as motivators and companions for children as well as determining the implementation of storytelling traditions at home. The tradition of storytelling increases children's religious values, marked by the child's ability to know God and his creation, love others and God's other creatures, get used to praying before and after activities, say and answer greetings, awareness of children to practice worship and the inculcation of morals and character. which is internalized in everyday life.